The prognostic nutritional index is associated with mortality of patients in intensive care unit - Kayhan, Sanem; Şimşek, Meltem; Gülsoy Kırnap, Nazlı (Journal of Surgery and Medicine, 2022)
Background/Aim: It has been reported that the prognostic nutritional index (PNI) is ), an immunonutritional index, associated with poor prognosis, especially in cardiovascular and malignant diseases. However, the clinical significance of PNI in intensive care (ICU) patients remains unclear. In this study, we aimed to measure the predictive value of the PNI in predicting mortality in patients hospitalized in the ICU. Methods: A total of 80 patients hospitalized in the internal medicine ICU of our hospital between January 2021 and September 2021 were included in this observational cohort study. The patients' demographic characteristics, comorbidities, laboratory parameters, need for and duration of mechanical ventilation, length of stay in ICU, and mortality rates were retrospectively analyzed. The patients were divided into two groups according to their survival; the first group comprised of survivors while the second group comprised of those who died in the ICU. The two groups were compared in terms of all variables. Results: The mean age of all subjects included in the study was 63 (18.2) years and 50% (n=40) were female and 50% (n=40) were male. When patients are grouped as survivors and non-survivors, the mean age and sex distribution were similar (P=0.23, P=0.27, respectively). The median follow-up period of the patients was 5 (IQR 3-11) days and the mortality rate was 38.7% (n=31). Those in the non-survivor group had higher APACHE II and SOFA scores (P=0.02, P<0.001, respectively), and a lower PNI level (P=0.01). In the multivariate regression analysis, PNI value [OR: 1.210 (95%CI: 1.048-1.396) P=0.009] was the negative independent risk factor and SOFA score [OR: 1.697 (95%CI: 1.201-2.398) P=0.03] was a positive independent risk factor. Conclusion: Despite our small cohort, we believe our findings corroborate our hypothesis that as a simple and inexpensive test, PNI is a useful biomarker to assess mortality risk in ICU patients.